Affekt Macht Netz - Slaby, Jan
Shit storms, hate speech or viral videos that promote clicking, linking, sharing: The linked society is driven by affects. The contributions included in this book examine the media-technological developments of our times and explore them from the perspective of a critical affect and social philosophy. They indicate that social media and digital platforms are not only spaces of exchange but also create affect economies - and therein lies their power. By creating new modalities of social interaction and therefore by determining the forms of articulation, they also change the political topography. Including a contribution by Antonio Negri
Keywords: Media studies; Gefühl; Digitale Revolution; Macht; Soziale Kontrolle; Sozialphilosophie; Big Data; Elektronische Überwachung; Datenanalyse; Gesellschaft; Personenbezogene Daten; Öffentlichkeit; Medienwissenschaft; Emotionales Verhalten; Politischer Protest; Privatheit; Soziologie; Social Media; Aufsatzsammlung